Regulasi Diri pada Budaya Hedonisme terhadap Pergaulan Bebas Kalangan Remaja di Indonesia - Ibnu Kaenah (Gunung Djati Conference Series, 2023)
This study aims to examine Epicuros' hedonistic ethics regarding self-control in the pleasures of life towards the phenomenon of adolescent lifestyle. This study answers the formulation of the problem about how to avoid and find solutions from the influence of self-regulation and a culture of hedonism on promiscuity among adolescents. A qualitative approach is used in this study and then the ethical theory of hedonism is used as a tool to analyze the phenomenon of this lifestyle action, because Epicurus' ethical theory of hedonism mostly discusses how humans should acquire and respond to the pleasures of life. The results of the research and discussion show that the motives of teenagers to have fun are to avoid stress, feelings of anxiety, and to get rid of feelings that disturb their peace. This study concludes that the lifestyle for fun among adolescents has an impact on not having a good learning ethic. So this fact requires serious handling to ensure a bright future for teenagers in Indonesia.